PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN METODE LATIHAN SIAP SISWA KELAS I C SD NEGERI 164 PEKANBARU - Nurzaili Nurzaili (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is classroom action research or classroom action research. The problem dealt with was from the low ability to complete thecount operations of grade I C SD Negeri 164 Pekanbaru. This learning problem is overcome by applying ready training methods. Theresearch aims to improve the ability of students to learn mathematics by applying ready training methods. Based on the results of researchand actions that by applying training methods are ready to be able to significantly improve learning outcomes in the IC SD Negeri 164Pekanbaru. Before the action is taken, the classical average value is 45.25, or unfavorably; in the first cycle to 61.25 or enough; and thesecond cycle becomes 81.50 or good. Before the action was carried out, students who completed their study at KKM 70 were only 13students or 32.50%; the first cycle becomes 22 students or 61.25%: and in the second cycle becomes 37 students or 92.50%. Based on theobservations of first-grade students of C SD Negeri 164 Pekanbaru, they seemed to understand the Ready Exercise Method and they couldwork independently in learning. The use of training methods is ready to successfully overcome the problem of the low mathematics learningoutcomes of students in the IC class of SD Negeri 164 Pekanbaru in the second cycle.